MANAJEMEN KOLABORASI ANTARA GURU DENGAN PESERTA DIDIK PADA KEGIATAN BELAJAR MENGAJAR ERA NEW NORMAL DI SMP NEGERI 1 LHOKSUKON ACEH UTARA - Wahyuni, Suci (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2022)
This study aims to find out how collaborative management between teachers and students in teaching and learning activities in the New Normal Era so that teaching activities run effectively. This research is located at SMP Negeri 1 Lhoksukon North Aceh which is a field study with a descriptive qualitative approach. The data source consists of primary and secondary data. Data collection techniques use observation, interviews and documentation. Data analysis is carried out by means of data reduction, data presentation and drawing conclusions on the data that has been collected. Meanwhile, to ensure the validity of the data, triangulation techniques are used with theory. The results of this study show that SMP Negeri 1 Lhoksukon North Aceh applies collaborative management in teaching and learning activities in this New Normal era by paying attention to several elements, including: First, the planning carried out in the New Normal Era was very different before the pandemic, the planning applied was that there must be a stable internet connection, short materials and self-study modules as well as the existence of a zoom application or google classroom. Second, the implementation must be in accordance with what has been planned at the initial stage as well as the participation of the learners themselves. Third, the assessment / evaluation used by SMP Negeri 1 Lhoksukon North Aceh is almost the same as before, namely the assessment at the beginning of learning and at the end of learning as well as the existence of daily tests and semester tests.